Zn–S Hybrid Batteries: Maximizing Energy Storage of Flexible Aqueous Batteries through Decoupling Charge Carriers (Adv. Energy Mater. 14/2021). Issue 14 (15th April 2021) - Dai, Chunlong; Jin, Xuting; Ma, Hongyun; Hu, Linyu; Sun, Guoqiang; Chen, Hao; Yang, Qiuju; Xu, Maowen; Liu, Qianwen; Xiao, Yukun; Zhang, Xinqun; Yang, Hongsheng; et al.
Abstract : In article number 2003982, Zhipan Zhang, Liangti Qu, and co‐workers decouple charge carriers in opposite electrodes to construct a new flexible aqueous Zn–S hybrid battery with ultrahigh specific capacity. This work sheds light on the development of more safe and durable energy storage devices for future flexible electronics.